A Hybrid Oral Rehabilitation of Hypohidrotic Ectodermal Dysplasia: A Conservative Approach with Three-Year Follow-Up - Aryen Kaushik; HarshVardhan Sinha; M. N. Hombesh; Pooja Rani; Taranjeet Kaur (Case Reports in Dentistry)
This case report presents a 19-year-old male patient with hypohidrotic ectodermal dysplasia, having a chief complaint of multiple missing teeth. Atraumatic extraction of the teeth with hopeless prognosis was done, and teeth with grade 2 mobility were submerged using cast dowel and coping. Following this, incremental increase in the vertical dimension was made using removable flexible splint of two-millimeter thickness. After facebow transfer and making appropriate eccentric bite records to program the semiadjustable articulator, wax-up was done at the desired vertical dimension (VD). The upper arch was finally restored using a long-span fixed partial denture and lower arch using bilateral attachment (Rhein 83) retained cast removable partial denture as a definitive prosthesis. Therefore, in conditions like hypodontia or oligodontia caused due to ectodermal dysplasia, attachment retained removable partial denture may prove beneficial by effectively distributing the occlusal forces. In clinical scenarios where implant is not feasible or not opted by the patient, this combination treatment may be a viable option.